the The Effect of Reward and Punishment on Employee Performance at PT Bank BTPN Tbk KCP Sumedang - Irfan Nur'arif, Muhammad; Damayanti, Wulan Ariani; Nurfajrina, Amalia (Ann Publisher, 2024)
Articles This research is based on a problem, namely there is a problem in the performance of employees of PT Bank BTPN Tbk KCP Sumedang. This study aims to determine the effect of rewards and punishments on employee performance at PT Bank BTPN Tbk KCP Sumedang. In this study, the researcher used a quantitative method by sampling using the saturated sampling method where all populations were used as samples, namely as many as 30 employees of PT Bank BTPN Tbk KCP Sumedang. In this study, the researcher used a research instrument, namely a questionnaire. The data analysis techniques used in this study are validity tests, reliability tests, and classical assumption tests (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression analysis, correlation coefficient test, datermination coefficient test, and hypothesis test (partial t test and simultaneous F test). The results of the study showed that rewards had a significant positive effect and punishment had a significant positive effect on the performance of employees of PT Bank BTPN Tbk KCP Sumedang. The magnitude of the Adjusted R Square value in the reward and punishmnet variables affecting employee performance is 46,8%.